Effect of ultrasound as pretreatment on the bioactive compounds in the hydrosol and condensate from the extraction of Agarwood bark: article - Abu Bakar, Nawal Syakirah; Che Radzi, Nurhaslina (2017)
The purpose of this study was to identify the effect of ultrasound as pretreatment on the bioactive compounds of Agarwood bark’s hydrosol and condensate. Most of the researches conducted on this plant only focused on the yield of essential oil of Agarwood, where the condensate and the hydrosol or plant water from the experiments were considered as wastes. However, the yield of essential oil obtained is little when compared to the total amount of Agarwood bark used for the extraction. To overcome this problem, a research is made on the hydrosol of Agarwood which was often disposed and discarded. This is to prove that the so-called waste is also as beneficial as the essential oils. The compounds in the hydrosol were identified to determine the benefits or uses for each compound. To enhance the transfer of compound from the wood to the solvent, a pretreatment was conducted on the wood. Ultrasound water bath equipment was used as pretreatment process while for extraction, hydro-distillation was selected. Pretreatment of grinded Agarwood with ultrasonic was done by adjusting the frequency between 12 kHz (Degas), 23 kHz (Pulse) and 46 kHz (Sweep), where ultrasonic for each frequency was done for 45 minutes, 60 minutes and 75 minutes. Hydro-distillation was performed after the pretreatment process. The effect of frequency from sonication towards the time taken to collect 200 ml of hydrosol was observed and the compounds from condensate and hydrosol were identified using Gas Chromatography Mass Spectrometry (GC-MS). The arsenic level for each hydrosol was also identified for its heavy metal using Induced Coupled Plasma- Mass Spectrometry (ICP-MS). The results indicated that the main compounds in the hydrosol and condensate are fatty acid and aromatic compounds. The mole percentage of each compound was also observed and evaluated. From the results and evaluation that has been done, it can be concluded that hydrosol and condensate contain beneficial bioactive compounds and can be used as by-product.